Rancang Bangun Alarm Pencegah Kebakaran Otomatis pada Rumah Menggunakan Sensor Api dan Asap - Syahrin, Elvin; Doni, Rahmad (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Fire is a disaster, generally caused more by negligence than the human itself with an impact on loss of property and property, even possibly causing casualties. A lot of data shows the incidence of fires that befell residential buildings. For this reason, a tool is designed that functions as a fire prevention tool by means of Arduino reading the MQ-2 gas sensor and fire sensor, if one of the sensors reads that there is a fire, the alarm will automatically sound and the water tap will open to minimize fires and extinguish fires as the first form of fire prevention.